The Challenges in the Provision of Counselling Services in Secondary Schools in Tanzania - Sima, Rebecca G. (Papers in Education and Development, 2018)
This is a research-based paper that uncovers the experiences and challenges in the provision of counselling services in secondary schools in Tanzania. The paper covers the main issues regarding adolescent secondary schools students and how they are affected by that developmental stage. It also points out how the then Ministry of Education and Culture (MoEC) took initiatives to train school counsellors for the purpose of establishing counselling services in schools. Training counsellors was one of the important aspects in implementing the provision of the service in schools. The main objective of the study was to find out what goes on the ground in relation to the provision of counselling services in schools after the training of school counsellors. Ninety six schools drawn from six regions were involved in the study. Using interviews, Focus Group Discussion (FGD) and observations, qualitative data were collected from school counsellors, students and Head of Schools (HoSs). Content analysis was used to analyse data. The findings revealed that counsellors were mainly challenged by the unavailability of counselling resources, including confidential rooms for conducting interviews. They had a high workload that limits their performance as counsellors. At the same time some counsellors were somewhat incompetent and in some cases Heads of Schools violated Ministry directive in selecting school counsellors. As one of the major recommendations, the author urges the Ministry of Education and Vocational Training (MoEVT) to provide counselling services in schools more strategically by providing schools with the required resources, including more seriously trained school counsellors to achieve its mission.